A case study on pollution and a human health risk assessment of heavy metals in agricultural soils around Sinop province, Turkey. (February 2020) - Baltas, Hasan; Sirin, Murat; Gökbayrak, Emre; Ozcelik, Ali Erdem
Abstract: In the present study, the concentration levels of heavy metals such as Cr, Fe, Ni, Cu, Zn, As and Pb in soil samples collected from 88 sampling locations around Sinop Province, Turkey were measured using energy dispersive X–ray fluorescence spectroscopy (EDXRF). To interpret and to evaluate the pollution status and distribution of heavy metals in soil, metal pollution parameters such as enrichment factor (EF), geo–accumulation index (Igeo ), pollution factor (CF) and pollution load index (PLI) and geo–spatial distribution patterns were used. The mean concentrations of Cr, Fe, Ni, Cu, Zn, As, and Pb were found to be 194.73, 39, 848.57, 85.02, 43.19, 65.10, 5.66, and 17.01 mg/kg, respectively. Results indicated that the mean concentrations of Cr, Ni, As, and Pb exceeded the world crustal average, with the exception of Fe, Cu, and As. Multivariate analysis results showed that Cr, Ni, Zn, As, and Pb levels in the investigated region were highly influenced by anthropogenic inputs such as agricultural practices. According to the health risk assessment model introduced by USEPA to evaluate the human health risks, the non–carcinogenic risk for children was above the threshold level, but low for adults. Total potential carcinogenic health risks for both children and adults in the study area were in acceptable range. Overall, when health risks are evaluated, it shows that children are more susceptible to non–carcinogenic and carcinogenic health effects of trace metals compared to adults. Highlights: Heavy metal concentrations were determined in soils of Sinop province using EDXRF. The soil metal contamination status is discussed using various pollution indices. The possible sources of metals were determined by multivariate statistical analysis. Geo–spatial distribution of heavy metals in soils were identified. A potential human health risk assessment was performed.